Molecular and Crystal Structure, Spectroscopic Properties of N-[4-(3-Methyl-3-Phenyl-Cyclobutyl)-Thiazol-2-yl]-N?-(1H-Pyrrol-2-Ylmethylene)-Hydrazine by Experimental Method and Quantum Chemical Calculation - Yuksektepe, Cigdem; Saracoglu, Hanife; Caliskan, Nezihe; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Taylor & Francis Ltd, 2010)
A new compound (C19H20N4S) has been synthesized and characterized by 1H nuclear magnetic resonance (NMR), 13C NMR, infrared (IR) and ultraviolet (UV)-visible spectroscopy, elemental analysis, and single crystal X-ray diffraction. The compound crystallizes in the triclinic space group P-1. The crystal structure is stabilized by N-H...N intermolecular hydrogen bonding. The optimized molecular geometry, vibrational frequencies, atomic charge distribution, and total energies of the title compound in the ground state have been calculated by using an ab initio method. A density functional theory (B3LYP) method with basis sets 6-311G (d, p) and 6-31G (d, p) was used in the calculations. Calculated frequencies and geometrical parameters are in good agreement with the corresponding experimental data. UV-Vis absorption spectra of the compound have been ascribed to their corresponding molecular structure and electrons orbital transitions. In addition, molecular electrostatic potential and thermodynamic parameters of the title compound were determined by the theoretical methods.
Keywords: Crystal structure; hydrazone; quantum Chemical calculation; thiazole